2021
DOI: 10.33225/jbse/21.20.927
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Validity and Reliability of Science Multiple Choice Test Using Rasch Dichotomous Measurement Model

Abstract: Multiple choice tests are widely applied to assess students’ knowledge in science education. This study aimed at assessing the validity and reliability of Science Multiple-choice Test in Malaysia. The items for this test were formulated by the researcher together with a panel of science teachers and the head of the science department with close reference to Secondary School Standard Curriculum (KSSM) syllabus. The test consists of 50 multiple-choice items with four options. Rasch measurement model was adopted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Regarding the proposed scale of science practices, the results revealed that the person reliability separation index was 2.01 and the person reliability was 0.80. The item separation index and the item reliability were 8.01 and 0.98 respectively, indicating an excellent level of reliability (MohdDzin& Lay, 2021).…”
Section: Discussionmentioning
confidence: 91%
“…Regarding the proposed scale of science practices, the results revealed that the person reliability separation index was 2.01 and the person reliability was 0.80. The item separation index and the item reliability were 8.01 and 0.98 respectively, indicating an excellent level of reliability (MohdDzin& Lay, 2021).…”
Section: Discussionmentioning
confidence: 91%
“…A Rasch measurement model (Bond & Fox, 2015;Liu, 2010;Mohd Dzin & Lay, 2021) to analyze the collected data using Winsteps software (Linacre, 2006) and SPSS. The reliability indices, difficulty estimates of test questions, infit and outfit statistics, and PTMEA correlations were estimated using Winsteps software.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…Almost all KCA instruments have been developed using the multiple-choice test (MCT) reaching 92.3% and the rest was developed with the MCT and multiple true false (MTF) format. MCT is a form of assessment that has been widely used in science education to investigate, identify, and assess students' understanding of certain science topics [41]. In fact, many other instruments assessment formats that can be developed include interviews, question test, question test and interviews, multiple choice test, and multiple-tier test.…”
Section: Methodsmentioning
confidence: 99%